Experimental study on the mixing and dispersing of floating particles in viscous system. (6th August 2016) - Liu, Baoqing; Zheng, Yijun; Chen, Mingqiang; Huang, Bolin; Jin, Zhijiang
Abstract: The effects of baffle configuration, impeller type, impeller diameter ratio, and immersion depth on the critical drawdown speed and power of floating particles were investigated by experiment, and the advantageous stirred vessel was determined on the basis of the low energy consumption principle. Furthermore, the effects of system viscosity, mean solid concentration, and particle size on the dispersing characteristic of floating particles were also researched with the advantageous stirred vessel. The results show that, (1) when the stirred vessel is equipped with a single baffle, the critical drawdown speed and power of floating particles are lower than those of others. (2) Among the propeller, six flat‐blade disc turbine (Rushton), and six 45° pitched‐blade turbine (PBT‐6), the Rushton turbine has the lowest critical drawdown speed, and the down‐pumping propeller (TXL) has the lowest critical drawdown power. (3) The critical drawdown speed and power are lower with a larger impeller diameter and a smaller immersion depth. (4) The critical drawdown speed and power increase with increasing system viscosity, mean solid concentration, and particle size. The experimental results provide useful guidelines for the advantageous design of the stirred vessel used for the dispersing of floating particles in a viscous system.